Implementation of Character Education at Madrasahs and Integrated Islamic Schools in Central Kalimantan - Surawan Surawan; Muhammad Syabrina; Cecep Zakariyas El Bilad; Asmail Azmy (Universitas Islam Negeri Mahmud Yunus Batusangkar, 2022)
This study aims to describe the implementation of character education at the madrasahs and integrated Islamic schools, namely at: SDIT Al-Ghazali, MIN 1 Palangka Raya, SMP-IT Al-Ghazali, MTsN 1 Palangka Raya, SMA-IT Hasanka and MAN Kapuas. The principals, teachers, parents and students were the research informants. Data were collected through participant observation, in-depth interview, and documentary study. The triangulation was used to check the trustworthiness of the data. The results showed that the implementation of discipline was by giving rewards and punishments according to school rules; honesty by using the Kantin Kejujuran and some CCTV, while hard work by using school assignments, group study and student work. Supporting and inhibiting factors include teachers, parents, students and the school environment. This finding confirms that schools have their own ways in applying character education based on each of their vision, need and condition. Any future research can be more directed at implementing character in Islamic madrasahs/schools, families, and communities so that they are able to provide role models and scientific treasures in this issue, considering that character is very important, especially in this age of character crisis among students.